The Role of Electrical Impedance Tomography in Lung Imaging - Anthony Christanto; Irma Darinafitri (Cermin Dunia Kedokteran, 2021)
Lung imaging in certain conditions, such as in patients with Acute Respiratory Distress Syndrome (ARDS), poses its challenges. Heterogeneity of lung damage in ARDS can only be detected by CT scan, causing treatment delay and increased mortality. Difficulty to perform standard imaging such as CXR in such patients also contributes to the increasing incidence of VALI (Ventilator-Associated Lung Injury) due to diagnosis delay. EIT (Electrical Impedance Tomography) is a novel imaging method that uses electrical impedance modality. EIT is a bedside, continuous imaging method which can depict both solids and fluids (including air) in body cavities, both statically and dynamically. EIT carries the potency to be the primary lung imaging method for patients in intensive care in the future.Pencitraan paru mempunyai tantangan tersendiri pada beberapa kondisi pasien, misalnya pada sindrom distres pernapasan akut (Acute Respiratory Distress Syndrome/ARDS). Heterogenitas kerusakan paru pada ARDS hanya bisa dideteksi menggunakan CT scan, mengakibatkan keterlambatan penanganan serta meningkatnya mortalitas. Kesulitan melakukan pencitraan standar seperti foto polos toraks juga turut berkontribusi dalam meningkatnya insidens VALI (Ventilator-Associated Lung Injury) karena keterlambatan diagnosis. EIT (Electrical Impedance Tomography) merupakan metode pencitraan baru menggunakan modalitas impedansi listrik. EIT dapat mencitrakan benda padat ataupun fluida (termasuk udara) dalam rongga tubuh dengan baik, baik secara statis maupun dinamis, secara kontinu (bedside). EIT berpotensi menjadi metode utama pencitraan paru pasien-pasien di perawatan intensif.